Corneal Sub‐Basal Nerve Plexus Assessment and its Association with Phenotypic Features and Lymphocyte Subsets in Sjögren's Syndrome - Barcelos, F (2022)
Purpose: To assess and compare corneal sub-basal nerve plexus morphology with circulating lymphocyte subsets, immunologic status and disease activity in Sjögren syndrome (SjS) patients. Methods: Fifty-five SjS patients, 63 Sicca patients (not fulfilling SjS criteria), 18 rheumatoid arthritis (RA) patients and 20 healthy controls (HC) were included. Systemic disease activity in SjS was assessed with the ESSDAI score. Lymphocyte subpopulations were studied with flow cytometry. Corneal confocal microscopy and ImageJ software were used to characterize corneal sub-basal nerve plexus in terms of nerve density (CNFD), length (CNFL) and tortuosity (CNFT). Conventional dry eye tests were also performed. Results: CNFL and CNFD were lower in SjS, Sicca and RA groups, compared to HC (p < 0.001 for both SjS and Sicca); CNFL p = 0.005, CNFD p = 0.018 in RA). CNFT was higher in SjS, followed by Sicca, RA and HC. A negative correlation was found between ESSDAI score and CNFL (r=-0.735, p = 0.012). CNFL correlated negatively with IL21+ CD8+ T cells (r=-0.279, p = 0.039) and a positively with total memory (r = 0.299, p = 0.027), unswitched memory (r = 0.281, p = 0.038) and CD24Hi CD27+ (r = 0.278, p = 0.040) B cells. CNFD showed a tendency to significance in its negative correlation with ESSDAI (r=-0.592, p = 0.071) and in its positive correlation with switched memory B cells (r = 0.644, p = 0.068). Conclusions: This is the first study aiming to correlate ocular findings with lymphocyte subsets in SjS. The associations founded between CNFL and CNFD and disease activity, IL21+ follicular T cells and some B-cell subsets suggest that corneal nerve damage may parallel systemic disease activity and inflammatory cells' dynamics.